2018
DOI: 10.1021/acs.inorgchem.7b03071
|View full text |Cite
|
Sign up to set email alerts
|

Slow Magnetic Relaxation in a Series of Mononuclear 8-Coordinate Fe(II) and Co(II) Complexes

Abstract: A series of homoleptic mononuclear 8-coordinate Fe and Co compounds, [Fe(L)](ClO) (2), [Fe(L)](ClO) (3), [Fe(L)](ClO) (4), [Co(L)](ClO) (5), [Co(L)](ClO) (6), [Co(L)](ClO) (7), and [Co(L)](ClO) (8) (L and L are 2,9-dialkylcarboxylate-1,10-phenanthroline ligands; L and L are 6,6'-dialkylcarboxylate-2,2'-bipyridine ligands), have been obtained, and their crystal structures have been determined by X-ray crystallography. The metal center in all of these compounds has an oversaturated coordination number of 8, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 107 publications
2
26
0
Order By: Relevance
“…The Zn─N distances are distributed in a narrow range of 2.048(5)–2.084(5) Å. The shorter Zn─N distances result in the relatively longer Zn─O bond lengths, which are in the range of 2.614–2.703 Å …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The Zn─N distances are distributed in a narrow range of 2.048(5)–2.084(5) Å. The shorter Zn─N distances result in the relatively longer Zn─O bond lengths, which are in the range of 2.614–2.703 Å …”
Section: Resultsmentioning
confidence: 99%
“…1 structurally resembles our recently reported Fe II and Co II complexes bearing the similar ligands. The Zn 2+ center is also 8‐coordinated by two symmetry‐related neutral tetradentate L via four N(diimine) and four O(carbomethoxy) atoms in a highly distorted square antiprism (D 4d ) . The degree of deviation from the standard square antiprism (D 4d ) was estimated from the continuous shape measures (CShMs) .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, compared to the universal hexacoordinated iron(II) complexes, coordination numbers for either the Fe II ion or the Fe III ion higher than six are rarely observed in discrete molecules because high coordination numbers are usually confined to the larger metal ions of the heavier f-elements rather than the comparatively lighter 3d ones. According to the Cambridge Structural Database (CSD; Groom et al, 2016), there are only about a dozen octacoordinated iron-based complexes which have been structurally characterized by single-crystal X-ray diffraction and most of them are iron(II) compounds (Long et al, 2015;Xiang et al, 2017;Jin et al, 2018;Seredyuk et al, 2015;Bu et al, 1998;Diebold & Hagen, 1998;de Martino Norante et al, 1992;Koch et al, 1996;Patra et al, 2010;Adam et al, 2016;Petzold et al, 2017;Singh et al, 1971), except for three examples based on the iron(III) ion reported over ten years ago (King et al, 1971;Koch et al, 1996;Patra et al, 2010). Recently, Jose and coworkers obtained two octacoordinated Fe II complexes using tetradentate tetrazole/triazole-based ligands, namely, [NEt 3 H]-[Fe{bipy(ttr) 2 }{Hbipy(ttr) 2 }]Á3MeOH [bipy(ttr) 2 is 6,6 0 -bis(1Htetrazol-5-yl)-2,2 0 -bipyridine] and [Fe(bptp) 2 ][BPh 4 ] 2 [bptp is bis(pyridyltriazolyl)pyridine] (Seredyuk et al, 2015;Adam et al, 2016), whose Fe II ions show a switch between a high-spin and a low-spin state within the measured temperature range.…”
Section: Introductionmentioning
confidence: 99%